Selectivity of nonsteroidal antiinflammatory drugs as inhibitors of constitutive and inducible cyclooxygenase. - Mitchell, J A (1993)
Constitutive cyclooxygenase (COX-1; prostaglandin-endoperoxide synthase, EC 1.14.99.1) is present in cells under physiological conditions, whereas COX-2 is induced by some cytokines, mitogens, and endotoxin presumably in pathological conditions, such as inflammation. Therefore, we have assessed the relative inhibitory effects of some nonsteroidal antiinflammatory drugs on the activities of COX-1 (in bovine aortic endothelial cells) and COX-2 (in endotoxin-activated J774.2 macrophages) in intact cells, broken cells, and purified enzyme preparations (COX-1 in sheep seminal vesicles; COX-2 in sheep placenta). Similar potencies of aspirin, indomethacin, and ibuprofen against the broken cell and purified enzyme preparations indicated no influence of species. Aspirin, indomethacin, and ibuprofen were more potent inhibitors of COX-1 than COX-2 in all models used. The relative potencies of aspirin and indomethacin varied only slightly between models, although the IC50 values were different. Ibuprofen was more potent as an inhibitor of COX-2 in intact cells than in either broken cells or purified enzymes. Sodium salicylate was a weak inhibitor of both COX isoforms in intact cells and was inactive against COX in either broken cells or purified enzyme preparations. Diclofenac, BW 755C, acetaminophen, and naproxen were approximately equipotent inhibitors of COX-1 and COX-2 in intact cells. BF 389, an experimental drug currently being tested in humans, was the most potent and most selective inhibitor of COX-2 in intact cells. Thus, there are clear pharmacological differences between the two enzymes. The use of such models of COX-1 and COX-2 activity will lead to the identification of selective inhibitors of COX-2 with presumably less side effects than present therapies. Some inhibitors had higher activity in intact cells than against purified enzymes, suggesting that pure enzyme preparations may not be predictive of therapeutic action.